Novel RAPF scheme and its performance of PAPR reduction and BER in FBMC‐OQAM system. Issue 13 (1st August 2019) - He, Zongmiao; Ling, Xiang; Zhou, Lingyu; Chen, Yiou; Yang, Yang
Abstract : Filter bank multicarrier with offset quadrature amplitude modulation (FBMC‐OQAM) has gained significant importance as a contender for the fifth generation mobile communication system and also meets the application requirements of the Internet of things. The peak‐to‐average power ratio (PAPR) of the FBMC‐OQAM is very high due to using a same prototype filter for each subcarrier and the addition of different subcarriers at the transmitter. Therefore, a novel randomly assigning prototype filter (RAPF) method is proposed to reduce PAPR in FBMC‐OQAM system. Based on the proposed RAPF method, the authors analyse the performances of both PAPR and bit error rate (BER) in the FBMC‐OQAM system. Simulation results show that the proposed RAPF method helps to significantly reduce PAPR of FBMC‐OQAM system. Meanwhile, compared with conventional FBMC‐OQAM system, the proposed RAPF‐FBMC‐OQAM scheme has almost the same BER performance in the additive white Gaussian noise channel but is descended slightly only in the high signal‐to‐noise ratio region of the frequency selective fading channel.